Mitochondrial DNA Evidence Supports the Hypothesis that Triodontophorus Species Belong to Cyathostominae - Gao, Yuan; Zhang, Yan; Yang, Xin; Qiu, Jian-Hua; Duan, Hong; Xu, Wen-Wen; Chang, Qiao-Cheng; Wang, Chun-Ren (Frontiers in Microbiology, 2017)
Equine strongyles, the significant nematode pathogens of horses, are characterized by high quantities and species abundance, but classification of this group of parasitic nematodes is debated. Mitochondrial (mt) genome DNA data are often used to address classification controversies. Thus, the objectives of this study were to determine the complete mt genomes of three Cyathostominae nematode species (Cyathostomum catinatum, Cylicostephanus minutus, and Poteriostomum imparidentatum) of horses and reconstruct the phylogenetic relationship of Strongylidae with other nematodes in Strongyloidea to test the hypothesis that Triodontophorus spp. belong to Cyathostominae using the mt genomes. The mt genomes of Cy. catinatum, Cs. minutus, and P. imparidentatum were 13,838 bp, 13,826 bp and 13,817 bp in length, respectively. Complete mt nucleotide sequence comparison of all Strongylidae nematodes revealed that sequence identity ranged from 77.8% to 91.6%. The mt genome sequences of Triodontophorus species had relatively high identity with Cyathostominae nematodes, rather than Strongylus species of the same subfamily (Strongylinae). Comparative analyses of mt genome organization for Strongyloidea nematodes sequenced to date revealed that members of this superfamily possess identical gene arrangements. Phylogenetic analyses using mtDNA data indicated that the Triodontophorus species clustered with Cyathostominae species instead of Strongylus species. The present study first determined the complete mt genome sequences of Cy. catinatum, Cs. minutus, and P. imparidentatum, which will provide novel genetic markers for further studies of Strongylidae taxonomy, population genetics, and systematics. Importantly, sequence comparison and phylogenetic analyses based on mtDNA sequences supported the hypothesis that Triodontophorus belongs to Cyathostominae.